2015
DOI: 10.1016/j.precamres.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Paleoarchean sulfur cycling: Multiple sulfur isotope constraints from the Barberton Greenstone Belt, South Africa

Abstract: a b s t r a c tMass-dependent and mass-independent sulfur isotope fractionation archived in volcanic and sedimentary rocks from the Barberton Greenstone Belt (3550-3215 Ma), South Africa, provide constraints for sulfur cycling on the early Earth. Four different sample suites were studied: komatiites and tholeiites, barite, massive and disseminated sulfide ores, and non-mineralized black shales.Variable but generally slightly positive ı 34 S values between −0.7 and +5.2‰, negative 33 S values between −0.50 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…Pyrites in the Mendon Formation show large isotope variability in δ 56 Fe, δ 34 S, and Δ 33 S, which is not related to the stratigraphic position within the core (Figure ). δ 34 S and Δ 33 S values range from −2.66 to +6.22‰ and −0.39 to +4.25‰, respectively (Figures and a), consistent with previous reports on the same formation (Galić et al, ; Montinaro et al, ; Roerdink, Mason, Whitehouse, & Reimer, ). The δ 56 Fe values vary from −4.02 to +2.54‰, covering almost the total terrestrial range reported so far (Dauphas, John, & Rouxel, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Pyrites in the Mendon Formation show large isotope variability in δ 56 Fe, δ 34 S, and Δ 33 S, which is not related to the stratigraphic position within the core (Figure ). δ 34 S and Δ 33 S values range from −2.66 to +6.22‰ and −0.39 to +4.25‰, respectively (Figures and a), consistent with previous reports on the same formation (Galić et al, ; Montinaro et al, ; Roerdink, Mason, Whitehouse, & Reimer, ). The δ 56 Fe values vary from −4.02 to +2.54‰, covering almost the total terrestrial range reported so far (Dauphas, John, & Rouxel, ).…”
Section: Resultssupporting
confidence: 91%
“…About 100 m of the uppermost Mendon Formation was recovered. The Mendon Formation was deposited between 3.34 and 3.26 Gyr and has been studied in detail (Busigny et al, ; Galić et al, ; Hofmann & Bolhar, ; Lowe & Byerly, ; Montinaro et al, ; Philippot et al, ; Philippot, Zuilen, & Rollion‐Bard, ; Tice et al, ; Trower & Lowe, ). The sequence consists of five volcanic cycles, termed Mv1 through Mv5, which are each capped by thin chert sequences, termed Mc1 through Mc5 (Byerly et al, ).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Hence, a key issue for elucidating the early Archean sulfur cycle concerns the significance of the isotopic composition of Archean barites. The main deposits in Australia and South Africa define a narrow range of both δ 34 S values between +3‰ and +8‰ and Δ 33 S anomalies between −0.1‰ and −1.2‰ (1,(5)(6)(7)(8)(9)(10)(11). In contrast to the δ 34 S values that are relatively constant in all barite deposits, the Δ 33 S values define a potential trend increasing from 3.5 (∼−1.5‰) to 3.2 Ga (∼−0.5‰; Fig.…”
mentioning
confidence: 99%
“…Montinaro et al. () have reported multiple sulfur isotopes of komatiite and tholeiite from the Barberton Greenstone Belt, South Africa, and showed limited variation in δ 34 S values. A multiple sulfur isotope study of amphibolites from the Isua supracrustal belt, which is believed to be the oldest oceanic crust, also shows a near‐zero δ 34 S signature (Siedenberg, Strauss, & Hoffmann, ).…”
Section: Introductionmentioning
confidence: 99%
“…The 34 S of the sulfide inclusions within the putative microbial textures is heavily depleted, and varies widely from −40‰ to −10‰ (McLoughlin, Grosch, Kilburn, & Wacey, 2012); the heterogeneity and magnitude of the sulfur isotope fractionation in the pillow lava support a microbial origin of sulfide, though the putative microbial textures may have been produced on the surface. Montinaro et al (2015) have reported multiple sulfur isotopes of komatiite and tholeiite from the Barberton Greenstone Belt, South Africa, and showed limited variation in δ 34 S values. A multiple sulfur isotope study of amphibolites from the Isua supracrustal belt, which is believed to be the oldest oceanic crust, also shows a near-zero δ 34 S signature (Siedenberg, Strauss, & Hoffmann, 2016).…”
mentioning
confidence: 99%